The Application Analysis of Occupational Safety and Health Management Systems in Building Construction Projects SMA Medika Samarinda - Benny Mochtar E Ariefien; Achmad Jaya Adhi Nugraha (Budapest International Research and Critics University, 2022)
In a building construction project, the occupational safety and health of each individual greatly influences the performance of the construction project. Based on data from Jamsostek Samarinda, the number of work accidents continues to increase every year. Therefore, to reduce the rate of work accidents, it is necessary to have an occupational safety and health management system (SMK3) to create occupational safety and health for workers in the hope of creating a safe, efficient and productive work environment. In this study, the source of data collection used was data from workers at the project site which was then analyzed using the Univariate analysis method. Based on the results of the study, the application of SMK3 to the use of work equipment and facilities as well as other aspects in the construction project of the SMK Medika Samarinda building, including the level of assessment of good implementation where the percentage of the effectiveness level of implementation reached a value of 79.87% based on Government Regulation of the Republic of Indonesia Number 50 of 2012.